Taxpayer Compliance and The Utilization of E-Samsat as Determinants of Regional Revenue Stability: A Study on Motor Vehicle Tax in Bulukumba - Ginting S, Chris Dayanti; Ginting, Wahyudi Pialanta (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2025)
Motor vehicle tax is one of the main sources of regional income and this research aims to determine the factors that influence taxpayer compliance in making motor vehicle tax (PKB) payments at the Bulukumba Samsat Office. The method used in this research is quantitative. The population used is all taxpayers registered at the Pare Samsat Bulukumba Office. The number of samples in this research was 100 respondents with sample determination using the technique purposive sampling. The data analysis technique used in this research is multiple linear regression analysis using the IBM SPSS Statistics version 30 program. The results of this research show that taxpayer awareness, tax service quality, and tax facilities influence motor vehicle taxpayer compliance. Meanwhile, taxpayer knowledge and tax sanctions have no effect on motor vehicle taxpayer compliance. Based on the results, the conclusion shows that the higher the level of taxpayer awareness, the better the quality of services and tax facilities provided can increase the ratio of taxpayer compliance with motor vehicle tax payments